2022
DOI: 10.1007/s11010-022-04601-2
|View full text |Cite
|
Sign up to set email alerts
|

Pooled evidence from preclinical and clinical studies for stem cell-based therapy in ARDS and COVID-19

Abstract: COVID-19 has severely devastated many lives across the globe. It has been speculated that stem cell-based therapy for COVID-19 treatment could be able to subsidize the effects. In preclinical and clinical studies, stem cell-based therapy has successfully eliminated inflammatory cytokines in ALI, ARDS, and COVID-19. Clinical trials have produced a variety of promising results for validating stem cell therapy in COVID-19 patients. For instance, exosome-based therapy (ExoFlow) showed an 87% survival status, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…More critically, there is no effective treatment for ARDS, a condition that develops and progresses rapidly and has high mortality [ 200 ]. For this reason, most of the clinical studies exploring the use of MSCs or their derivatives are conducted in ARDS patients [ 200 , 201 ]. However, these studies were carried out with a relatively small number of enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…More critically, there is no effective treatment for ARDS, a condition that develops and progresses rapidly and has high mortality [ 200 ]. For this reason, most of the clinical studies exploring the use of MSCs or their derivatives are conducted in ARDS patients [ 200 , 201 ]. However, these studies were carried out with a relatively small number of enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following that, we searched for articles related to COVID-19. It has been found that the aetiology, pathology, transmission, treatment and consequences of COVID-19 had been well-published in the current literature (Murugan & Rangasamy, 2022;Nontawong et al, 2022;Qu et al, 2020;Valdes et al, 2022). Managing COVID-19 and reducing its harm had absorbed substantial medical resources and the energy of hospital managers (Ding & Zhao, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%